South African traditional healers' organisations in the context of traditionalism and modernity - Fenyves, Katalin (My University, 1994)
This research report seeks to explore the issues surrounding the organisation of traditiional healers and how their world views can be contextualised within tradtionalism and modernity. [Abbreviated Abstract. Open document to view full version]
A Research Report submitted to the Faculty of Arts, Department of Sociology, University of the Witwatersrand, Johannesburg, in partial fulfillment for the degree of Master of Arts. Johannesburg, 1994
Keywords: Healers--South Africa.; Herbalists--South Africa; Medicine--South Africa; Transcultural medical care--South Africa; Social medicine--South Africa